Pilot-scale residual sludge dehydration in a convective rotary dryer, Case: Santa clara wastewater treatment plant, Lima, Perú: Santa Clara Water Treatment Plant, Lima Province, Peru - Natividad Marin, Leynard (2023)
This research aims to decrease the moisture and pathogen content in a residual sludge from Santa Clara wastewater treatment plant. This could reduce transport cost to sludge disposal centers and its reuse as a possible fertilizer. The pilot scale dehydration was developed with a system comprised by rotatory convective dryer, agitating tank, screw conveyor, air heating furnace, cyclone collector and a gas scrubber. The effect of temperature (120°C, 150°C y 200°C) and sludge residence time within the dryer drum was studied. The initial sludge, with 85.90%, 9.17% y 4.93% in moisture, volatile suspended solids and non-volatiles suspended solids, achieved a minimum moisture of 17.74% when a temperature of 200°C and 60 minutes residence time were applied. Helminths eggs were not detected in the initial sludge, but a high Escherichia Coli concentration was found (4×105 NMP/1g ST to 1.6×107 NMP/1g ST), therefore, the addition of  was needed to rise the pH to 12 during the initial sludge feeding to the dryer. The dried sludge characterization showed a high nutrient (N, P, C, etc.) concentration, indicating some advantages as a fertilizer, but its high metal content also suggests more research if it is used in food crops production.